Developing and predicting of early mortality after endovascular thrombectomy in patients with acute ischemic stroke - Chen, Yimin; Zhou, Sijie; Yang, Shuiquan; Mofatteh, Mohammad; Hu, Yuqian; Wei, Hongquan; Lai, Yuzheng; Zeng, Zhiyi; Yang, Yajie; Yu, Junlin; Chen, Juanmei; Sun, Xi; et al. (Frontiers in Neuroscience, 2022)
Background: Stroke is one of the leading causes of mortality across the world. However, there is a paucity of information regarding mortality rates and associated risk factors in patients with acute ischemic stroke (AIS) undergoing endovascular thrombectomy (EVT). In this study, we aimed to clarify these issues and analyzed previous publications related to mortality in patients treated with EVT. Methods: We analyzed the survival of 245 consecutive patients treated with mechanical thrombectomy for AIS for which mortality information was obtained. Early mortality was defined as death occurring during hospitalization after EVT or within seven days following hospital discharge from the stroke event. Results: Early mortality occurred in 22.8% of cases in this cohort. Recanalization status (modified thrombolysis in cerebral infarction, mTICI) (p = 0.002), National Institute of Health Stroke Scale Score (NIHSS) score 24-hours after EVT (p < 0.001) and symptomatic intracerebral hemorrhage (sICH) (p < 0.001) were independently associated with early mortality. Age, sex, cardiovascular risk factors, NIHSS score pre-treatment, Alberta Stroke Program Early CT Score (ASPECTS), stroke subtype, site of arterial occlusion and timing form onset to recanalization did not have an independent influence on survival. Non-survivors had a shorter hospitalization (p < 0.001) but higher costs related to their hospitalization and outpatient care. Conclusions: The recanalization status, NIHSS score 24-hours after EVT and sICH were predictors of early mortality in AIS patients treated with EVT.